Financial Education - Strategy to Combat Tax Evasion - Oana Oprișan; Ana-Maria Dumitrache (Șerbănescu); Adrian Moroșan (Ovidius University Annals: Economic Sciences Series, 2022)
In most countries, one of the reasons for economic problems is the extent of tax evasion in its various forms. Tax evasion is the way in which economic agents respond to tax pressure when they exceed a certain threshold necessary for starting, maintaining and developing their business or any other gainful activity and in relation to their current wealth or income. Tax evasion can be said to be a social phenomenon with financial implications, including the partial or total use of legislative loopholes or the use of financial strategies or engineering to evade tax obligations. The main aim of this research was to check the tax education of both firms and employees. The specific objectives of this work are to present the factors and methods of combating tax evasion, the underground economy and the phenomenon of corruption, as well as the possibilities of reducing and keeping tax evasion under control.